Organizational Commitment and Ethical Behavior: An Empirical Study of Information System Professionals - Oz, Effy (Journal of business ethics, 2001)
IS professionals have been reported to have one of the highest turnover rates. They have also often been accused of unethical conduct, specifically, pirating software, hacking, giving professional opinion that exceeds their knowledge, and not protecting people's privacy. In a sample of 71 IS professionals and 250 members of other professions we found that IS professionals were more committed to their organizations than the other professionals, and that IS professionals were, indeed, less ethical with respect to software piracy and hacking. However, we found that they were not less ethical regarding professional opinions that exceed one's knowledge and protecting people's privacy.